The Indonesian Supreme Court’s Recognition of the Right to Customary Land in Indonesia: Pengakuan Mahkamah Agung Indonesia terhadap Hak Atas Tanah Adat di Indonesia - Matara, Opa Jermias; Tjempaka, Tjempaka (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Customary land rights remain a central issue in Indonesian agrarian law because communal land ownership must be positioned within both national land regulation and living customary norms. Specific Background The dispute over Pusako Tinggi land in Supreme Court Decision Number 3569 K/Pdt/2024 reflects a legal conflict between clan-based inheritance claims and the authority of a customary council over communal customary land. Knowledge Gap The legal protection of indigenous peoples’ rights in this case required further clarification, particularly regarding how formal evidentiary standards interact with customary legitimacy in determining rights over Pusako Tinggi land. Aims This study analyzes the protection of indigenous peoples’ rights to Pusako Tinggi land and the legal consequences of Supreme Court Decision Number 3569 K/Pdt/2024 for customary land protection. Results The findings show that photocopied documents without verified authenticity and de auditu testimony had no evidentiary strength, while the customary council’s evidence established stronger legal and customary legitimacy. The decision recognized the customary council as the legitimate holder of customary land authority and rejected individual claims that were not supported by valid proof. Novelty This study demonstrates that judicial recognition of customary land rights depends not only on normative acknowledgment of indigenous rights but also on authentic evidence, collective authority, and customary legitimacy. Implications The decision supports legal certainty, protects communal land from individual transfer, preserves the social function of Pusako Tinggi land, and emphasizes the need for stronger customary land documentation. Highlights: Photocopied documents and indirect testimony failed to prove lawful ownership. Collective authority received stronger judicial acknowledgment than individual claims. Formal proof remains essential for protecting inherited communal property. Keywords: Protection, Indigenous Peoples, High Heritage Land, Customary Council of the Nagari.